Distinction between contrast staining and hemorrhage after endovascular stroke treatment: one CT is not enough. (1st April 2016) - Dekeyzer, Sven; Nikoubashman, Omid; Lutin, Bart; De Groote, Jeroen; Vancaester, Evelien; De Blauwe, Sofie; Hemelsoet, Dimitri; Wiesmann, Martin; Defreyne, Luc
Abstract : Background: Postinterventional cerebral hyperdensities (PCHDs) are a common finding after endovascular stroke treatment. There is uncertainty about the extent to which PCHDs correspond to hemorrhage or contrast staining. Our aim was to evaluate the use of PCHD density on immediate postinterventional CT, and PCHD evolution on follow-up CT for differentiating contrast staining from hemorrhage after endovascular treatment. Methods: We retrospectively reviewed the imaging data of 84 patients who underwent endovascular treatment for acute arterial ischemic stroke in the anterior circulation and who received an immediate postinterventional CT, a follow-up CT within 36 h, and a follow-up MRI within 10 days. Results: PCHDs were seen in 62 of 84 patients in a total of 130 Alberta Stroke Program Early CT Score (ASPECTS) areas. A specificity of 100% to predict hemorrhage was only seen for PCHDs with densities <40 HU (for ruling hemorrhage out) and ≥140 HU (for ruling hemorrhage in), at the cost of a low sensitivity of 1.1% and 2.4%, respectively. Persisting PCHDs correlated with hemorrhage with a specificity of 93.3% and a sensitivity of 62.5%. When follow-up CT was performed at least 19 h after the first CT, persisting PCHDs correlated with hemorrhage with a specificity of 100% and a sensitivity of 62.5%. Conclusions: There are no density thresholds for PCHDs that allow predicting the absence or presence of hemorrhage with 100% specificity and acceptable sensitivity. A CT scan performed at least 19–24 h after endovascular therapy is the only reliable method to differentiate contrast staining from hemorrhage.